THE LITERATURE AND THE RESEARCH HISTORY: THE GYMNASTICS IN THE ATENEU'S RAUL POMPEIA (Fiep Bulletin - online, 2015)
The objective this article is to search one comprehension of the social space of the gymnastics in them last days of Brazilian monarch in the Ateneu's Raul Pompéia (1863 1895) and dialogue with the Ceara' s Ateneu School. The presences of the gymnastic and swimming, as well as told infantile and swinging are portraires in the workmanship, considered one of most important of the Brazilian realism. Of character autobiography, the writer portraies, main personage, the Sergio's young, lived in the internal school in the époque the end the monarch for begging of Republic .As documentary source, literature is a way of reconstruction of history. Still that it requires the care of no absolute it as only truth. The literature helps the reflections on the human body, the playful one, the sport and the itself Education Physique, preventing, thus, the fragmentation the one that these knowledge had been overwhelmed.
Keywords: RESEARCH HISTORY; EDUCATION PHYSIQUE; O ATENEU.